Modification and repair combined waste lithium ion battery graphite negative electrode material regeneration method

Through the combination of modification and repair, the graphite negative electrode material in waste lithium-ion batteries was successfully recycled and recycled, solving the problems of graphite resource waste and environmental pollution, and achieving an efficient, low-cost and low-pollution recycling process.

CN119481398APending Publication Date: 2025-02-18TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424906.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle and reuse graphite negative electrode materials in waste lithium-ion batteries, resulting in waste of graphite resources and environmental pollution.

Method used

By combining modification and repair, the graphite negative electrode material of the used lithium-ion battery is discharged and disassembled in a saturated salt solution, and then treated in a mixed solution of deionized water and anhydrous ethanol, and further carried out in an acid solution. The reaction was carried out, and nitrogen source modification reagent was added, and finally heat treatment was carried out under an inert gas atmosphere to obtain the regenerated modified graphite negative electrode active material.

Benefits of technology

It realizes effective impurity removal and material modification of waste graphite negative electrode materials, improves the structural stability and electrochemical performance of recycled materials, reduces recycling costs, solves the high energy consumption and high pollution problems of traditional ignition recycling, and significantly reduces the Greenhouse effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481398A_ABST
    Figure CN119481398A_ABST
Patent Text Reader

Abstract

The invention provides a modification and repair combined waste lithium ion battery graphite negative electrode material regeneration method, which is characterized by comprising the following steps: soaking a waste lithium ion battery in a saturated salt solution, completely discharging, and disassembling to obtain a graphite negative electrode sheet; then soaking the graphite negative electrode plate in a mixed solution of deionized water and absolute ethyl alcohol, carrying out suction filtration on the graphite negative electrode material filtrate to obtain a filter cake, washing the filter cake with water, drying and grinding to obtain graphite powder; the graphite powder is subjected to acid leaching treatment and then diluted; and adding a nitrogen source modification reagent into the diluted mixed solution, carrying out suction filtration on the obtained mixed solution of the modified graphite material to obtain the modified graphite material, drying, grinding, putting into a tubular furnace, heating in an inert gas atmosphere, carrying out heat preservation, and cooling to room temperature to obtain the modified graphite negative electrode active material. The method is simple in production process, low in reagent and environment cost and low in energy consumption, and has positive significance on recycling treatment of retired batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and the field of waste battery recycling, and specifically relates to a method for regenerating graphite negative electrode materials of waste lithium ion batteries by combining modification and repair. Background Art

[0002] Lithium-ion batteries were first successfully developed and commercialized by Sony Corporation of Japan in the early 1990s. They have the advantages of high energy density, long cycle life and excellent safety performance, and are widely used in 3C electronic products, new energy vehicles and large-scale grid energy storage. However, batteries usually need to be retired after 3-5 years of service due to the decline in performance and safety. At the same time, the price of lithium has risen sharply, and waste lithium-ion batteries are called "urban mines" because of their extremely high content of valuable metals (lithium, iron, cobalt, etc.). Therefore, the waste battery recycling industry has broad prospects and huge potential. How to recycle retired lithium-ion batteries with high efficiency, low pollution and low cost has become an important challenge facing the battery industry development strategy.

[0003] In waste lithium-ion batteries, graphite negative electrode materials fail and age after hundreds of charge and discharge cycles. The failure mechanism includes the co-embedding of interlayer solvent molecules, which leads to excessive growth and thickening of the SEI surface coating layer or rupture to form a porous structure, the growth of lithium dendrites piercing the diaphragm, and the corrosion of copper current collectors. Waste graphite materials cannot be directly reused in lithium-ion batteries under normal circumstances. They must be recycled through impurity removal and structural repair. However, the current research on waste lithium-ion battery recycling technology in the industry tends to be more inclined to the recovery of valuable metals in positive electrode materials. As the main component of the battery negative electrode, graphite materials are usually directly abandoned. In traditional methods, they are usually burned as a carbon source to produce a high-temperature environment or used as a reducing agent for valuable metal elements, resulting in serious waste of graphite resources and secondary environmental pollution. The recycling and reuse of negative electrode materials can not only reduce the cost of raw materials and bring higher economic benefits to the synthesis of new materials, but also reduce environmental problems caused by excessive mining and high purification of graphite mines.

[0004] Therefore, developing a method for regenerating waste lithium-ion battery graphite negative electrode materials that combines modification and repair is an urgent problem to be solved and has important economic and environmental significance. Summary of the invention

[0005] The present invention is made to solve the above-mentioned problem, and aims to provide a method for regenerating graphite negative electrode materials of waste lithium-ion batteries by combining modification and repair.

[0006] The invention provides a method for regenerating graphite negative electrode materials of waste lithium ion batteries by combining modification and repair, which is used for recovering graphite negative electrode active materials in waste lithium ion batteries and has the following characteristics: step S1, immersing the waste lithium ion batteries in a saturated salt solution for discharge, disassembling to obtain graphite negative electrode sheets after the discharge is complete, and placing the graphite negative electrode sheets in a ventilated environment to remove residual electrolyte; step S2, immersing the graphite negative electrode sheets in a mixed solution of deionized water and anhydrous ethanol, filtering to obtain a current collector copper foil and a graphite negative electrode material filtrate, filtering the graphite negative electrode material filtrate to obtain a filter cake, washing the filter cake with water, drying it, grinding it, and sieving it to obtain a stone Ink powder; step S3, under heating conditions, immersing the graphite powder in an acid solution, reacting under stirring / ultrasound assistance to obtain a mixed solution, and slowly adding a diluent to the mixed solution to dilute it to obtain a diluted mixed solution; step S4, then adding a nitrogen source modification reagent to the diluted mixed solution, keeping the temperature unchanged and continuously stirring / ultrasound treating the reaction for a period of time to obtain a mixed solution of modified graphite material; step S5, filtering the mixed solution of the modified graphite material to obtain a modified graphite material, and after drying and grinding the modified graphite material, putting it into a tubular furnace, heating it under an inert gas atmosphere and then keeping it warm, and then cooling it to room temperature to obtain a regenerated modified graphite negative electrode active material.

[0007] The method for regenerating graphite negative electrode materials of waste lithium-ion batteries by combining modification and repair provided by the present invention may also have the following characteristics: in step S1, the waste lithium-ion batteries are any waste lithium-ion batteries with recycling value that have reached the retirement level; the graphite negative electrode sheets are graphite negative electrode sheets obtained by conventional discharge and disassembly, newly made graphite negative electrode sheets, graphite negative electrode sheet scraps, graphite negative electrode sheets that have not undergone charge and discharge cycles after electrolyte injection, or graphite negative electrode sheets that have undergone multiple charge and discharge cycles; and the saturated salt solution is any one or more of NaCl, FeSO4, Na2SO4, MnSO4, (NH4)2SO4, and Na2CO3.

[0008] The modification and repair combined waste lithium ion battery graphite negative electrode material regeneration method provided by the present invention can also have the following characteristics: wherein, in step S2, when the soaking treatment process is performed, the stirring / ultrasonic rate is a stirring speed of 0-200 r / min, the ultrasonic power is 0-100%, the soaking time is 0.5-5h, the temperature of the mixed solution of deionized water and anhydrous ethanol is 25-60°C, the mass ratio of deionized water to anhydrous ethanol is 100:(10-100), the solid-liquid ratio of the graphite negative electrode sheet to the mixed solution is 1:(10-100), the filtering method is centrifugal or suction filtration, and when the filter cake is washed, the detergent is deionized water, and the number of washing times is 3-5 times.

[0009] The modification and repair combined waste lithium-ion battery graphite negative electrode material regeneration method provided by the present invention can also have the following characteristics: in step S2, during the drying process, the drying temperature is 50-120° C., the drying time is 6-12 hours, the filter screen used in the screening process is 100-800 mesh, and the particle size of the graphite powder is 1-10 mm.

[0010] The modification and repair combined waste lithium ion battery graphite negative electrode material regeneration method provided by the present invention can also have the following characteristics: wherein, in step S3, when the graphite powder is immersed in an acid solution for reaction, the reaction temperature is 30-200°C, the reaction time is 4-6h, the stirring speed is 100-500r / min, the ultrasonic power is 10%-100%, the acid solution is any one or more of HCl, HNO3, H2SO4, HCOOH, CH3COOH, C3H6O3, C6H8O7, C2H2O4, C7H6O3, the concentration of the acid solution is 0.5mol / L-18.4mol / L, and the solid-liquid ratio of the graphite powder to the acid solution is 1:(10-50).

[0011] The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair provided by the present invention can also have the following characteristics: in step S4, the reaction temperature is 30-200°C, the reaction time is 20-30h, the nitrogen source modification reagent is any one or more of CO(NH2)2, C3H6N6, NH4Cl, NH4HCO3, (NH4)2CO3, the diluent is deionized water, the volume ratio of the diluent is (0-10):1, and the concentration of the diluted mixed solution is 0.5-5mol / L.

[0012] The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair provided by the present invention may also have the following characteristics: in step S5, during the drying process of the modified graphite material, the drying temperature is 50-120°C, the drying time is 8-15h, and after the modified graphite material is placed in a tubular furnace, the reaction temperature is 400-1200°C, the heating rate is 3-5°C / min, and the insulation time is 1-10h.

[0013] The modification and repair combined waste lithium ion battery graphite negative electrode material regeneration method provided by the present invention may also have the following characteristics, wherein the inert gas is nitrogen or argon.

[0014] Functions and Effects of the Invention

[0015] According to a modification and repair combined waste lithium ion battery graphite negative electrode material regeneration method involved in the present invention, it includes the following steps: first, the waste lithium ion battery is immersed in a saturated salt solution for discharge, and after the discharge is complete, the graphite negative electrode sheet is disassembled; after ventilation and drying, the graphite negative electrode sheet is immersed in a mixed solution of ionized water and anhydrous ethanol for treatment, and after filtering, a current collector copper foil and a graphite negative electrode material filtrate are obtained, and the graphite negative electrode material filtrate is filtered to obtain a filter cake, and the filter cake is washed with water, dried, ground, and sieved to obtain graphite powder; and then, the graphite is heated under heating conditions. The powder is immersed in an acid solution, and reacted under stirring / ultrasound assistance to obtain a mixed solution; then a diluent is slowly added to the mixed solution for dilution, and then a nitrogen source modification reagent is added to the diluted mixed solution, the temperature is kept constant, and stirring / ultrasound treatment is continued for a period of time to obtain a mixed solution of modified graphite material; finally, the mixed solution of the modified graphite material is filtered to obtain a modified graphite material, and the modified graphite material is placed in a tubular furnace after drying and grinding, heated and kept warm in an inert gas atmosphere, and then cooled to room temperature to obtain a regenerated modified graphite negative electrode active material. In this process, the reagents used, such as saturated salt solution, deionized water, ethanol, sulfuric acid or hydrochloric acid solution, are relatively low in cost. The stirring / ultrasound and the filtration used multiple times are simple to operate. Under low reagent cost and temperature environment, the impurity removal and material modification of waste negative electrode materials can be achieved in one step, and the residual binder and other high-molecular impurities in the waste graphite material can be decomposed. At the same time, the surface coating modification of the regenerated negative electrode material can be achieved, and the structural stability and electrochemical properties of the recycled material can be improved, which further significantly reduces the recycling cost of lithium-ion battery negative electrode materials, solves the high energy consumption and high pollution problems of traditional pyrometallurgical recycling, and significantly reduces the greenhouse effect.

[0016] In summary, this method has a simple production process, low reagent cost, environmental cost and energy consumption, and has positive significance for improving the electrochemical performance of regenerated negative electrode materials and the recycling and utilization of retired batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 X-ray diffraction patterns of the modified graphite negative electrode active material and the waste graphite negative electrode active material obtained in Example 1 of the present invention;

[0018] Figure 2 Transmission electron microscope pictures of the modified graphite negative electrode active material and the waste graphite negative electrode active material obtained in Example 1 of the present invention;

[0019] Figure 3 Electrochemical cycle performance test diagram of a half-cell assembled from the modified graphite negative electrode active material obtained in Example 1 of the present invention and a waste battery:

[0020] Figure 4This is an electrochemical rate performance diagram of a half-cell assembled from the modified graphite negative electrode active material obtained in Example 1 of the present invention and a waste battery. DETAILED DESCRIPTION

[0021] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments and the accompanying drawings specifically illustrate a method for regenerating waste lithium-ion battery graphite negative electrode materials that combines modification and repair of the present invention.

[0022] <Example 1>

[0023] This embodiment provides a method for regenerating graphite negative electrode materials of waste lithium-ion batteries by combining modification and repair, which specifically includes the following steps:

[0024] Step 1: soak any waste lithium-ion battery with recycling value and reaching the retirement level in any one or more of NaCl, FeSO4, Na2SO4, MnSO4, (NH4)2SO4, and Na2CO3 for discharge, disassemble to obtain graphite negative electrode sheet after complete discharge, and place the graphite negative electrode sheet in a ventilated environment to remove residual electrolyte. In this embodiment, the specific experimental process is as follows:

[0025] The commercial retired lithium iron phosphate power battery was immersed in a saturated NaCl solution for discharge, disassembled to obtain a graphite negative electrode sheet, and the obtained graphite negative electrode sheet was placed in a ventilated environment for 1-2 days to remove some residual electrolyte.

[0026] Step 2: Place the graphite negative electrode sheet disassembled in step 1 in a mixed solution of deionized water and anhydrous ethanol and soak it for 0.5-5h under stirring / ultrasonic conditions, wherein the reaction temperature is 25-60°C, preferably 30-40°C, the mass ratio of deionized water to anhydrous ethanol is 100:(10-100), the mass ratio is preferably 100:(40-60), the solid-liquid ratio of the graphite negative electrode sheet to the mixed solution is 1:(10-100), and the current collector copper is obtained after filtration. The graphite negative electrode material filtrate is filtered to obtain a filter cake, the filter cake is washed with water 3-5 times, dried and ground, the drying temperature is 50-120°C, preferably the drying temperature is 60-80°C, the drying time is 6-12h, preferably the drying time is 8h, and the graphite powder is obtained after sieving, the filter screen used for sieving is 100-800 mesh, preferably 200-500 mesh, and the particle size of the obtained graphite powder is 1-10mm, preferably 5-7mm in diameter. In this embodiment, the specific experimental process is as follows:

[0027] The graphite negative electrode sheet disassembled in step one is soaked in a deionized water / ethanol mixture at a temperature of 25°C for 30 minutes, the mass ratio of deionized water to ethanol is 2:1, and the mass ratio of the graphite negative electrode sheet to the mixture is 1:30. After the infiltration, the current collector copper foil and the graphite negative electrode material filtrate are obtained by filtration. The graphite negative electrode material filtrate is filtered to obtain a filter cake, and the filter cake is washed with deionized water for 3 times during the filtration process. The treated graphite negative electrode material filter cake is dried at 80°C for 8 hours. After drying, the filter cake is ground and crushed, and then sieved to obtain graphite powder.

[0028] Step 3, soaking the graphite powder obtained in step 2 in any one or more of HCl, HNO3, H2SO4, HCOOH, CH3COOH, C3H6O3, C6H8O7, C2H2O4, C7H6O3 with a concentration of 0.5mol / L-18.4mol / L, at a reaction temperature of 30-200°C, preferably a reaction temperature of 60-80°C, a stirring rate of 100-500r / min, more preferably 400r / min, if ultrasound is used, the power of ultrasound is 10%-100% to react to obtain a mixed solution, slowly adding a diluent to the mixed solution to dilute it to obtain a diluted mixed solution with a concentration of 0.5-5mol / L, and the solid-liquid ratio of graphite powder to acid solution is 1: (10-50), more preferably 1: 10. In this embodiment, the specific experimental process is as follows:

[0029] The graphite powder obtained in step 2 is immersed in concentrated sulfuric acid for reaction, wherein the solid-liquid ratio of the graphite powder to the concentrated sulfuric acid is 1:10, the reaction temperature is 60°C, the stirring speed is 400r / min, and the reaction time is 5h. After the reaction, a mixed solution is obtained, and deionized water is slowly added to the mixed solution for dilution to obtain a diluted mixed solution with a concentration of 3mol / L.

[0030] Step 4: Add any one or more of CO(NH2)2, C3H6N6, NH4Cl, NH4HCO3, (NH4)2CO3 to the diluted mixed solution obtained in step 3, keep the reaction temperature at 30-200°C and continue stirring / ultrasonic treatment for 10-30h to obtain a mixed solution of modified graphite material. In this embodiment, the specific experimental steps are as follows:

[0031] To the diluted mixed solution obtained in step 3, add urea powder with a molar ratio of sulfuric acid to urea of ​​1:3.6, maintain the reaction temperature at 60° C. for 24 hours, and obtain a mixed solution of modified graphite material.

[0032] Step 5, the mixed solution of the modified graphite material obtained in step 4 is filtered to obtain a modified graphite material, and the modified graphite material is placed in a tube furnace after drying and grinding. During the drying process of the graphite material, the drying temperature is 50-120°C, more preferably 60-80°C, and the drying time is 8-15h, more preferably 8h. After heating in a nitrogen or argon atmosphere, it is kept warm, and then cooled to room temperature to obtain a regenerated modified graphite negative electrode active material. In the tube furnace, the reaction temperature is 400-1200°C, more preferably 600-700°C, the heating rate is 3-5°C / min, the insulation time is 1-10h, and the insulation time is more preferably 1-2h. In this embodiment, the specific experimental process is as follows:

[0033] The mixed solution of the modified graphite material obtained in step 4 is filtered to obtain the modified graphite material. The modified graphite material is dried and ground and then placed in a tubular furnace. The temperature is raised from room temperature to 600°C at 5°C / min in an argon atmosphere, and the temperature is kept for 2 hours. The regenerated modified graphite negative electrode active material is obtained after the furnace is cooled to room temperature.

[0034] Figure 1 The X-ray diffraction diagrams of the modified graphite negative electrode active material and the waste graphite negative electrode active material obtained in Example 1 of the present invention.

[0035] like Figure 1 As shown, the characteristic peaks of the modified graphite negative electrode active material obtained in Example 1 of the present invention are consistent with the graphite standard PDF card #41-1487.

[0036] Figure 2 The transmission electron microscope pictures of the modified graphite negative electrode active material and the waste graphite negative electrode active material obtained in Example 1 of the present invention are taken.

[0037] like Figure 2 As shown, the modified graphite negative electrode active material obtained in Example 1 of the present invention has a complete graphite layered lattice structure and an obvious amorphous surface coating layer.

[0038] <Example 2>

[0039] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, except that the solid-liquid ratio of graphite powder to acid solution in step 3 is different and the dilution concentration after acid leaching is different. The operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same and will not be elaborated here. In this embodiment, the specific experimental process of step 3 is as follows:

[0040] Step three, soaking the graphite powder obtained in step two in concentrated sulfuric acid for reaction, wherein the solid-liquid ratio of graphite powder to concentrated sulfuric acid is 1:20, the reaction temperature is 60°C, the stirring speed is 400r / min, and the reaction time is 5h. After the reaction is completed, a mixed solution is obtained, and deionized water is slowly added to the mixed solution for dilution to obtain a diluted mixed solution with a concentration of 1 mol / L.

[0041] <Example 3>

[0042] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the ratio of the nitrogen source modifying reagent in step 4 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 4 is as follows:

[0043] Step 4: Add urea powder with a molar ratio of sulfuric acid to urea of ​​1:1.8 to the diluted mixed solution obtained in step 3, maintain the reaction temperature at 60° C. for 24 hours, and obtain a mixed solution of modified graphite material.

[0044] <Example 4>

[0045] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the mixed solution after acid leaching is not diluted in step 3, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 3 is as follows:

[0046] Step three, soaking the graphite powder obtained in step two in concentrated sulfuric acid for reaction, wherein the solid-liquid ratio of graphite powder to concentrated sulfuric acid is 1:20, the reaction temperature is 60°C, the stirring speed is 400r / min, and the reaction time is 5h. After the reaction is completed, a mixed solution is obtained, which is directly used in the next reaction without dilution.

[0047] <Example 5>

[0048] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the concentration of the acid solution used for acid leaching in step 3 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 3 is as follows:

[0049] Step three, soaking the graphite powder obtained in step two in 3 mol / L dilute sulfuric acid for reaction, wherein the solid-liquid ratio of graphite powder to dilute sulfuric acid is 1:20, the reaction temperature is 60°C, the stirring speed is 400r / min, the reaction time is 5h, and a mixed solution is obtained after the reaction is completed.

[0050] <Example 6>

[0051] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the concentration of the acid solution used for acid leaching in step 3 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 3 is as follows:

[0052] Step 3: soak the graphite powder obtained in step 2 in 1 mol / L dilute sulfuric acid for reaction, wherein the solid-liquid ratio of graphite powder to dilute sulfuric acid is 1:20, the reaction temperature is 60°C, the stirring speed is 400r / min, the reaction time is 5h, and a mixed solution is obtained after the reaction is completed.

[0053] <Comparative Example 1>

[0054] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the reaction temperature in the tube furnace in step 5 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 5 is as follows:

[0055] Step 5, the mixed solution of the modified graphite material obtained in step 4 is filtered to obtain a modified graphite material, the modified graphite material is dried and ground, and then placed in a tubular furnace, heated from room temperature to 500°C at 5°C / min in an argon atmosphere, kept warm for 2 hours, and cooled to room temperature with the furnace to obtain a regenerated modified graphite negative electrode active material.

[0056] <Comparative Example 2>

[0057] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the reaction temperature in the tube furnace in step 5 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 5 is as follows:

[0058] Step 5, the mixed solution of the modified graphite material obtained in step 4 is filtered to obtain a modified graphite material, the modified graphite material is dried and ground, and then placed in a tubular furnace, heated from room temperature to 700°C at 5°C / min in an argon atmosphere, kept warm for 2 hours, and cooled to room temperature with the furnace to obtain a regenerated modified graphite negative electrode active material.

[0059] <Comparative Example 3>

[0060] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the reaction temperature in the tube furnace in step 5 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 5 is as follows:

[0061] Step 5, the mixed solution of the modified graphite material obtained in step 4 is filtered to obtain a modified graphite material, the modified graphite material is dried and ground and placed in a tubular furnace, the temperature is increased from room temperature to 900°C at 5°C / min in an argon atmosphere, and the temperature is kept for 2 hours, and the furnace is cooled to room temperature to obtain a regenerated modified graphite negative electrode active material.

[0062] <Comparative Example 4>

[0063] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the modified graphite material in step 5 is not subjected to subsequent heat treatment, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 5 is as follows:

[0064] Step 5: Filter the mixed solution of the modified graphite material obtained in step 4 to obtain a modified graphite material. After drying and grinding, the modified graphite material is placed in a tubular furnace and kept warm for 2 hours at room temperature under an argon atmosphere to obtain a regenerated modified graphite negative electrode active material.

[0065] <Comparative Example 5>

[0066] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the concentration and type of the acid solution used for acid leaching in step 3 are different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of step 3 is as follows:

[0067] Step three, soaking the graphite powder obtained in step two in 3 mol / L dilute hydrochloric acid for reaction, wherein the solid-liquid ratio of graphite powder to dilute hydrochloric acid is 1:20, the reaction temperature is 60°C, the stirring speed is 400r / min, the reaction time is 5h, and a mixed solution is obtained after the reaction is completed.

[0068] <Comparative Example 6>

[0069] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the concentrated sulfuric acid in step 3 is replaced by 3 mol / L dilute hydrochloric acid and the type of nitrogen source modification reagent in step 4 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of steps 3 and 4 is as follows:

[0070] Step three, soaking the graphite powder obtained in step two in 3 mol / L dilute hydrochloric acid for reaction, wherein the solid-liquid ratio of graphite powder to dilute hydrochloric acid is 1:20, the reaction temperature is 60°C, the stirring speed is 400r / min, the reaction time is 5h, and a mixed solution is obtained after the reaction is completed.

[0071] Step 4: add ammonium chloride powder with a molar ratio of hydrochloric acid to ammonium chloride of 1:3.6 to the diluted mixed solution obtained in step 3, maintain the reaction temperature at 60° C. for 24 hours, and obtain a mixed solution of modified graphite material.

[0072] <Comparative Example 7>

[0073] In this embodiment, based on the preparation conditions of Example 1, the specific implementation process of this embodiment is the same as that of Example 1, the only difference is that the acid solution in step 3 is replaced with deionized water and the type of nitrogen source modification reagent in step 4 is different, and the operation methods, dosages, experimental conditions, etc. of the remaining steps are exactly the same, which will not be elaborated here. In this embodiment, the specific experimental process of steps 3 and 4 is as follows:

[0074] Step three, soaking the graphite powder obtained in step two in deionized water for reaction, wherein the solid-liquid ratio of graphite powder to deionized water is 1:20, the reaction temperature is 60°C, the stirring speed is 400r / min, the reaction time is 5h, and a mixed solution is obtained after the reaction is completed.

[0075] Step 4: add urea powder with a concentration of 8 M to the mixed solution obtained in step 3, keep the reaction temperature at 60° C. and react for 24 hours to obtain a mixed solution of modified graphite material.

[0076] <Experimental Example 1>

[0077] In this experimental example, the regenerated modified graphite negative electrode active material obtained in Example 1 was assembled into a CR2025 button-type half-cell, and the performance of the CR2025 button-type half-cell was tested.

[0078] The process inside a CR2025 button cell half-cell is as follows:

[0079] The graphite negative electrode active material, conductive agent and polyvinylidene fluoride (PVDF) binder obtained in Example 1 were mixed in a ratio of 8:1:1, and 1-methyl-2-pyrrolidone (NMP) was added. After stirring evenly, the mixture was evenly coated on a copper foil. The copper foil was vacuum dried at 80°C for 12 hours, and the dried electrode was punched into a disc with a diameter of 12 mm using a punching machine. The loading amount of the graphite negative electrode active material on the copper foil was about 1.3-1.5 mg / cm 2Lithium sheets were used as counter and reference electrodes, 25um microporous Celegard2400 single-layer polypropylene (PP) was used as the separator, and the electrolyte formula was 1 mol of LiPF6 dissolved in a solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) with a volume ratio of 1:1:1 and containing 1% vinylene carbonate (VC) additive. CR2025 button cells were assembled in an argon-filled glove box.

[0080] The button cell test system of Shenzhen Xinwei was used to test the cycle performance and rate performance. The button half-cell was charged and discharged at a constant current rate of 0.2C (1C = 372mA / g) with a voltage range of 0.001-3V (vs Li / Li+).

[0081] Figure 3 This is a test diagram of the electrochemical cycle performance of a half-cell assembled from the modified graphite negative electrode active material obtained in Example 1 of the present invention and a waste battery.

[0082] like Figure 3 As shown, the half-cell assembled from the modified graphite negative electrode active material obtained in Example 1 was tested to have a 0.2C first discharge capacity of 384 mAh / g, which is significantly improved compared with the waste battery.

[0083] Figure 4 This is an electrochemical rate performance diagram of a half-cell assembled from the modified graphite negative electrode active material obtained in Example 1 of the present invention and a waste battery.

[0084] like Figure 4 As shown, the half-cell assembled from the modified graphite negative electrode active material obtained in Example 1 has excellent electrochemical rate performance.

[0085] <Experimental Example 2>

[0086] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Experimental Example 1, except that the regenerated modified graphite negative electrode active material prepared in Example 2 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Example 2 is tested to have a 0.2C first discharge specific capacity of 356 mAh / g.

[0087] <Experimental Example 3>

[0088] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Experimental Example 1, except that the regenerated modified graphite negative electrode active material prepared in Example 3 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Example 3 is tested to have a 0.2C first discharge specific capacity of 351 mAh / g.

[0089] <Experimental Example 4>

[0090] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Experimental Example 1, except that the regenerated modified graphite negative electrode active material prepared in Example 4 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Example 4 is tested to have a 0.2C first discharge specific capacity of 368 mAh / g.

[0091] <Experimental Example 5>

[0092] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Experimental Example 1, except that the regenerated modified graphite negative electrode active material prepared in Example 5 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Example 5 is tested to have a 0.2C first discharge specific capacity of 330 mAh / g.

[0093] <Experimental Example 6>

[0094] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Experimental Example 1, except that the regenerated modified graphite negative electrode active material prepared in Example 6 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Example 6 is tested to have a 0.2C first discharge specific capacity of 326 mAh / g.

[0095] <Experimental Example 7>

[0096] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Comparative Example 1, except that the regenerated modified graphite negative electrode active material prepared in Comparative Example 1 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Comparative Example 1 is tested to have a 0.2C first discharge specific capacity of 324 mAh / g.

[0097] <Experimental Example 8>

[0098] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Comparative Example 2, except that the regenerated modified graphite negative electrode active material prepared in Comparative Example 2 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Comparative Example 2 is tested to have a 0.2C first discharge specific capacity of 332 mAh / g.

[0099] <Experimental Example 9>

[0100] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Comparative Example 3, except that the regenerated modified graphite negative electrode active material prepared in Comparative Example 3 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Comparative Example 3 is tested to have a 0.2C first discharge specific capacity of 349 mAh / g.

[0101] <Experimental Example 10>

[0102] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Comparative Example 4, except that the regenerated modified graphite negative electrode active material prepared in Comparative Example 4 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Comparative Example 4 is tested to have a 0.2C first discharge specific capacity of 311 mAh / g.

[0103] <Experimental Example 11>

[0104] The method of assembling a half-cell and the method of performing performance testing on the half-cell in this experimental example are exactly the same as those in Comparative Example 5, except that the regenerated modified graphite negative electrode active material prepared in Comparative Example 5 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Comparative Example 5 is tested to have a 0.2C first discharge specific capacity of 319 mAh / g.

[0105] <Experimental Example 12>

[0106] The method of assembling half-cells and the method of performance testing half-cells in this experimental example are exactly the same as those in Comparative Example 6, except that the regenerated modified graphite negative electrode active material prepared in Comparative Example 6 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Comparative Example 6 is tested to have a 0.2C first discharge specific capacity of 348 mAh / g.

[0107] <Experimental Example 13>

[0108] The method of assembling half-cells and the method of performance testing half-cells in this experimental example are exactly the same as those in Comparative Example 7, except that the regenerated modified graphite negative electrode active material prepared in Comparative Example 7 is used to assemble the original cell, and the half-cell assembled from the modified graphite negative electrode active material obtained in this Comparative Example 7 is tested to have a 0.2C first discharge specific capacity of 331 mAh / g.

[0109] Functions and Effects of the Embodiments

[0110] Combined with the test results of each experimental example, it can be seen that the half-cell performance is greatly improved after acid leaching, nitridation treatment and high-temperature heat treatment. Different modification methods and different high-temperature heat treatment conditions are selected to explore the influence on the regenerated waste graphite negative electrode materials. It further illustrates that the regeneration method of waste lithium-ion battery graphite negative electrode materials combined with modification and repair provided by us is low-cost, low-energy consumption, environmentally friendly, simple in process and has excellent performance.

[0111] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for regenerating graphite negative electrode materials of waste lithium-ion batteries by combining modification and repair, which is used to recover graphite negative electrode active materials in waste lithium-ion batteries, characterized in that: The following steps are involved: Step S1, immersing the waste lithium-ion battery in a saturated salt solution for discharge, disassembling the battery after the discharge is complete to obtain a graphite negative electrode sheet, and placing the graphite negative electrode sheet in a ventilated environment to remove residual electrolyte; Step S2, immersing the graphite negative electrode sheet in a mixed solution of deionized water and anhydrous ethanol, filtering to obtain a current collector copper foil and a graphite negative electrode material filtrate, filtering the graphite negative electrode material filtrate to obtain a filter cake, washing the filter cake with water, drying it, grinding it, and sieving it to obtain a graphite powder; Step S3, immersing the graphite powder in an acid solution under heating conditions, reacting under stirring / ultrasound assistance to obtain a mixed solution, and slowly adding a diluent to the mixed solution to dilute it to obtain the diluted mixed solution; Step S4, then adding a nitrogen source modifying reagent to the diluted mixed solution, keeping the temperature constant and continuously stirring / ultrasonicating the reaction for a period of time to obtain a mixed solution of modified graphite material; Step S5, filtering the mixed solution of the modified graphite material to obtain the modified graphite material, and placing the modified graphite material into a tubular furnace after drying and grinding, heating it under an inert gas atmosphere and then keeping it warm, and then cooling it to room temperature to obtain the regenerated modified graphite negative electrode active material.

2. The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair according to claim 1, characterized in that: in, In step S1, the waste lithium-ion battery is any waste lithium-ion battery with recycling value that has reached the retirement level. The graphite negative electrode sheet is a graphite negative electrode sheet obtained by conventional disassembly, a newly manufactured graphite negative electrode sheet, a graphite negative electrode sheet scrap, a graphite negative electrode sheet that has not been subjected to charge and discharge cycles after electrolyte injection, or a graphite negative electrode sheet that has been subjected to multiple charge and discharge cycles; The saturated salt solution is any one or more of NaCl, FeSO4, Na2SO4, MnSO4, (NH4)2SO4, and Na2CO3.

3. The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair according to claim 1, characterized in that: in, In step S2, during the soaking process, the stirring speed is 0-200 r / min, and the ultrasonic power is 0-100%. The soaking time is 0.5-5h. The temperature of the mixed solution of deionized water and anhydrous ethanol is 25-60°C. The mass ratio of the deionized water to the anhydrous ethanol is 100:(10-100), The solid-liquid ratio of the graphite negative electrode sheet to the mixed solution is 1:(10-100), The filtering method is centrifugal or suction filtration. When washing the filter cake, the detergent is deionized water, and the washing times are 3-5 times.

4. The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair according to claim 1, characterized in that: in, In step S2, during the drying process, the drying temperature is 50-120°C and the drying time is 6-12h. The filter used in the screening process is 100-800 mesh. The particle size of the graphite powder is 1-10 mm.

5. The method for regenerating waste lithium-ion battery graphite negative electrode material by combining modification and repair according to claim 1, characterized in that: in, In step S3, when the graphite powder is immersed in the acid solution for reaction, the reaction temperature is 30-200°C, the reaction time is 4-6h, the stirring speed is 100-500r / min, and the ultrasonic power is 10%-100%. The acid solution is any one or more of HCl, HNO3, H2SO4, HCOOH, CH3COOH, C3H6O3, C6H8O7, C2H2O4, C7H6O3, The concentration of the acid solution is 0.5 mol / L-18.4 mol / L, The solid-to-liquid ratio of the graphite powder to the acid solution is 1:(10-50).

6. The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair according to claim 1, characterized in that: in, In step S4, the reaction temperature is 30-200°C and the reaction time is 20-30h. The nitrogen source modification reagent is any one or more of CO(NH2)2, C3H6N6, NH4Cl, NH4HCO3, (NH4)2CO3, The diluent is deionized water, The volume ratio of the diluent is (0-10): 1, The concentration of the diluted mixed solution is 0.5-5 mol / L.

7. The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair according to claim 1, characterized in that: in, In step S5, during the drying process of the modified graphite material, the drying temperature is 50-120° C. and the drying time is 8-15 hours. After the modified graphite material is placed in the tubular furnace, the reaction temperature is 400-1200° C., the heating rate is 3-5° C. / min, and the insulation time is 1-10 h.

8. The method for regenerating waste lithium-ion battery graphite negative electrode materials by combining modification and repair according to claim 1, characterized in that: in, The inert gas is nitrogen or argon.